Small bowel adenocarcinomas with favorable prognoses by radical resection and adjuvant chemotherapy: a case series of five cases - Yuri Nishioka; Yasunori Matsumoto; Shunsuke Imanishi; Satoshi Endo; Takeshi Toyozumi; Yoshihiro Kurata; Takuma Sasaki; Gaku Ohira; Koichi Hayano; Hisahiro Matsubara (Surgical Case Reports)
Abstract Background Small bowel cancer is very rare, accounting for less than 5% of all gastrointestinal cancers, and small bowel adenocarcinoma accounts for approximately 40% of all small bowel cancers. Small bowel adenocarcinoma is often found in advanced stages, with only 40–65% of cases being curatively resectable. The prognosis is poor, with a 5-year survival rate of 14–33% for all patients and 40–60% for those who are curatively resectable. In Japan, practice guidelines for duodenal cancer were instituted in 2021. However, evidence-based standard treatments have not been established for jejunal and ileal cancers. In particular, chemotherapeutic options are limited, and there are only a few reports on multidisciplinary treatments, including adjuvant chemotherapy. Case presentation We report five cases of jejunal or ileal lesions that were treated with adjuvant chemotherapy after radical resection. Three patients were male and two were female, with a median age of 67 years. Tumor localization was observed in the jejunum in all cases. Clinical staging was as follows: stage IIIA in two cases and stage IIIB in three cases. Laparotomy was then performed in all cases, employing partial resection with lymph node dissection. Pathological staging in all cases was as follows: stage IIB in two cases, stage IIIA in one case, and stage IIIB in two cases. In all cases, the regimen for adjuvant chemotherapy was selected based on the colorectal cancer guidelines. No serious complications arose from adjuvant therapy; however, adverse events occurred in patients receiving multi-agent chemotherapy. No recurrence was observed in any of the cases, and all the patients survived, with a median survival time of 32 months. As a representative case, we present a case of adjuvant chemotherapy for jejunal adenocarcinoma staged as pT3N2M0, pStage IIIB, with no recurrence at 32 months postoperatively. Conclusions In general, favorable outcomes were achieved with adjuvant therapy applied in accordance with the criteria for colorectal cancer. These favorable outcomes suggest that it is necessary to identify the risk factors and indications for adjuvant therapy, specifically for small bowel adenocarcinoma.